A Test of an Instrument for Measuring the Organisational Survival of the Retail Food Business in Thailand - Auyporn Naklamthong; Wornchanok Chaiyasoonthorn; Singha Chaveesuk (My University, 2023)
In Thailand, competition in the retail business tends to be very intense because entrepreneurs in this business and from other businesses, as well as new competitors, both inside and outside the country, recognise the potential for growth in the Thai retail sector. This research aimed to test an instrument for measuring organisational survival by studying, examining, and reviewing the literature in the form of books, journals, and related research to develop questions used as an instrument for collecting data from a sample group of retail food businesses in Thailand. The instrument was validated by 5 research and statistics experts in the retail food business. The index of item-objective congruence (IOC) for all questions was more than 0.5, indicating the usability of the instrument. Afterwards, the researchers performed a pilot study to test the reliability of the instrument and make improvements. The improved questionnaire was then utilised to collect data from 30 sample respondents, after which the collected data were evaluated to assess the reliability by analysing the Cronbach's alpha coefficient at a confidence interval of 95%. The results of the analysis showed that the Cronbach's alpha coefficient was 0.971 overall, which was at an acceptable level. Thus, the instrument could be used to measure the factors influencing the organisational survival of retail food businesses in Thailand during the COVID-19 pandemic.
Keywords: Competitor analysis; Sample (material); Working Capital and Financial Performance